Pencemaran Lingkungan Akibat Pembakaran Batok Kelapa dalam Perspektif Pidana - Dhea Ifanda Mantali; Fenty Puluhulawa; Suwitno Yutye Imran (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This article aims to determine the role of Law of the Republic of Indonesia No. 32 of 2009 concerning environmental protection and management towards the environment in Tambo'o Village which is experiencing environmental damage and pollution. This article also examines the factors that hinder the implementation of environmental pollution sanctions due to coconut shell burning and the implementation of criminal sanctions for environmental pollution according to Law Number 32 of 2009. In this study, the author uses an empirical legal research method. Namely by directly observing the field to obtain data related to coconut shell burning in Tambo'o Village. This study uses a descriptive approach in analyzing the data obtained. This study was conducted with residents who were selected purposively (sampling). The results of this study indicate that the role of Law of the Republic of Indonesia No. 32 of 2009 concerning environmental protection and management towards the environment in Tambo'o Village has not run according to expectations. And the factors that hinder the implementation of sanctions are due to weak law enforcement and suboptimal law enforcement. Many complaints from residents about the condition of their environment that has been polluted by smoke produced from burning coconut shells and the perpetrators have never been sanctioned by the government because of the lack of community and government participation in reporting cases of environmental pollution around them. The resolution of the deliberation is not good and stops there.